2012
DOI: 10.1177/156482651203300307
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Iodine Content in Table Salt Consumed in Democratic Republic of Congo

Abstract: Background. DR Congo has adopted universal salt iodization to reduce disorders due to iodine deficiency. Since 1994, only (IQR, 19.0 ppm (IQR, in semiurban areas, and 20.1 ppm (IQR,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
6
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
3
6
1
1
Order By: Relevance
“…The estimated proportion of households with an adequate level of iodine in Arba Minch town, 52.8%, was higher compared to the sub-national estimate for SNNPR, 13.7% [7], and also compared to a study in Wolaita zone, 37.7% [9]. Our sample, however, was restricted to households located in an urban area, and different studies reported a higher level of iodine content in urban than rural areas [9,[13][14][15]. Consistent with our finding, a study in southwest Ethiopia, Dera district, reported that 57.4% of households had an adequately iodized salt (≥ 15 ppm) [16].…”
Section: Discussionmentioning
confidence: 64%
“…The estimated proportion of households with an adequate level of iodine in Arba Minch town, 52.8%, was higher compared to the sub-national estimate for SNNPR, 13.7% [7], and also compared to a study in Wolaita zone, 37.7% [9]. Our sample, however, was restricted to households located in an urban area, and different studies reported a higher level of iodine content in urban than rural areas [9,[13][14][15]. Consistent with our finding, a study in southwest Ethiopia, Dera district, reported that 57.4% of households had an adequately iodized salt (≥ 15 ppm) [16].…”
Section: Discussionmentioning
confidence: 64%
“…In a study on iodine content of salt table that we conducted with our colleagues in Lubumbashi, Kitwa et al found that median iodine content was lower than the minimum threshold of 15 ppm in >36 % of samples, and that there was still non-iodized salt commercialized in Lubumbashi ( 17 ) . They also found lower iodine content values in rural areas: the proportion of non-iodized salt commercialized was greater than in urban and semi-urban areas.…”
Section: Discussionmentioning
confidence: 97%
“…No data are available in Congolese pregnant women, despite the increase in iodine needs in this particular group. In a study by Kitwa et al , median iodine content of table salt consumed by women in Lubumbashi was found to be between 19·0 and 20·5 ppm; and non-iodized salt was still commercialized, as 13·9 % of table salt samples had no detectable iodine ( 17 ) . In a pilot study conducted in 2007, we measured UIC in spot urine samples from fifty pregnant women attending antenatal consultations, and we observed 42 % of women with UIC below 150 μg/l, 26 % with UIC between 150 μg/l and 249 μg/l, 26 % with UIC between 250 μg/l and 499 μg/l, and 6 % with UIC above 500 μg/l (MK Kalenga and A Robert, unpublished results).…”
mentioning
confidence: 99%
“…In Morocco, Zahidi et al reported no significant difference in iodine concentration between urban and rural areas [21]. However, in Democratic Republic of Congo and Pakistan, the results reported by Kitwa et al and Bhutta et al, respectively, revealed differences between rural areas and urban area with higher percentages of compliance in this latter [22,23]. Iodized salts from Senegalese households showed lower level of compliance with the recommended WHO/UNICEF/ICCIDD level (15 ppm) than that from households of some sub-Saharan countries except Niger and Ghana [17,18,[24][25][26].…”
Section: Discussionmentioning
confidence: 92%